A morphologic study of the airway structure abnormalities in patients with asthma by high-resolution computed tomography - Wang, Dan; Luo, Jian; Du, Wen; Zhang, Lan-Lan; He, Li-Xiu; Liu, Chun-Tao (Journal of Thoracic Disease, 2016)
Background: Airway structure changes, termed as airway remodeling, are common in asthma patients due to chronic inflammation, which can be assessed by high-resolution computed tomography (HRCT). Considering the controversial conclusions in the correlation of morphologic abnormalities with clinical feature and outcome, we aimed to further specify and evaluate the structural abnormalities of Chinese asthmatics by HRCT. Methods: From August 2012 to February 2015, outpatients with asthma were recruited consecutively in the Asthma Center of West China Hospital, Sichuan University. Standard HRCT and pulmonary function test (PFT) were performed to collect information of bronchial wall thickening, bronchial dilatation, mucus impaction, emphysema, mosaic perfusion, atelectasis, and spirometric parameters. We reported the incidence of each structural abnormality in HRCT and compared it among different asthmatic severities. Results: A total of 123 asthmatics were enrolled, among which 84 (68.3%) were female and 39 (31.7%) were male. At least one structural abnormality was detected by HRCT in 85.4% asthmatics, and the incidence of bronchial wall thickening, bronchial dilatation, mucus impaction, emphysema, mosaic perfusion, and atelectasis was 57.7%, 51.2%, 22%, 24.4%, 5.7% and 1.6%, respectively. The incidences of bronchial wall thickening, bronchial dilation and emphysema were significantly increased by asthma severity (P